Contributions of body fat, fat free mass and arm muscle area in athletic performance of wheelchair basketball players - Lúcia Oliveira; Saulo Oliveira; Fernando Guimarães; Manoel Costa (Desafio Singular, 2017)
The aims of this study were: to verify the relationship (1) and dependency (2) between body fat (BF), fat free mass (FFM) and the arm muscle area (AMA) with athletic performance of wheelchair basketball players. Twenty-two subjects were evaluated according to the following order, in 24-hour intervals: a) anthropometric measurements and the Wingate anaerobic test (day 1); b) assessment of VO2peak and threshold (2); and c) specific tests (3). The results showed satisfactory relationships of AMA with handgrip left (r=.36; p=.08), VO2peak (r=.59; p=.03), medicine ball throwing (r=.54; p=.00), absolute (r=.61; p=.00) and relative anaerobic power (r=.67; p=.00). BF with handgrip left (r= .43; p=.03), medicine ball throwing (r=.50; p=.01), absolute (r=.77; p=.00) and relative (r=.82; p=.00) anaerobic power. And FFM with handgrip (r=.44; p=.03), medicine ball throwing (r=.43; p=.03), absolute (r=.64; p=.00) and relative (r=.69; p= .00) anaerobic power. The regression analyses revealed that only predictive models by AMA presented good determination coefficients to VO2peak (r2=.35; p=.00), medicine ball throwing (r2=.29; p=.00), absolute (r2=.37; p=.00) and relative (r2=.46; p=.00) anaerobic Power. The results indicated the importance to consider some anthropometric measures, in particular muscular tissue, to sport training and athletic performance evaluation of wheelchair basketball players.